2017
DOI: 10.1177/0044118x17697235
|View full text |Cite
|
Sign up to set email alerts
|

Mentor Response to Youth Academic Support–Seeking Behavior

Abstract: Mentoring-based interventions for adolescent offenders are promising strategies for reducing the likelihood of academic underachievement, truancy, and school dropout. Program effectiveness, however, varies widely. Investigation into factors that strengthen the impact of mentoring on academic-related outcomes is warranted. One factor might be academic attunement, or the degree to which a mentor's emphasis on academics is consistent with youth's academic support-seeking behavior and desire for academic help. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 34 publications
0
8
0
1
Order By: Relevance
“…Mentees’ perceptions of support and help from their mentors, happiness, and mentor satisfaction were positively associated with the mentees’ academic outcomes (e.g., liking school, scholastic efficacy, grades, education plans), social outcomes (e.g., social acceptance, parental trust, social support from parents, siblings, and other adults), and emotional outcomes (e.g., hope) in BBBS in Ireland [ 61 ]. Mentees with attuned mentors (i.e., exhibiting an ongoing capacity to identify and flexibly meet mentees’ needs; [ 62 ], who participated in a 12-week time-limited mentoring program, reported greater value for school, academic self-efficacy, and truancy, as compared with mentees with poorly attuned mentors [ 63 ]. Perceived mentors’ help and mentees’ dissatisfaction, the latter feeling hurt and betrayed, accounted for poor mentee outcomes in BBBS [ 18 ].…”
Section: Resultsmentioning
confidence: 99%
“…Mentees’ perceptions of support and help from their mentors, happiness, and mentor satisfaction were positively associated with the mentees’ academic outcomes (e.g., liking school, scholastic efficacy, grades, education plans), social outcomes (e.g., social acceptance, parental trust, social support from parents, siblings, and other adults), and emotional outcomes (e.g., hope) in BBBS in Ireland [ 61 ]. Mentees with attuned mentors (i.e., exhibiting an ongoing capacity to identify and flexibly meet mentees’ needs; [ 62 ], who participated in a 12-week time-limited mentoring program, reported greater value for school, academic self-efficacy, and truancy, as compared with mentees with poorly attuned mentors [ 63 ]. Perceived mentors’ help and mentees’ dissatisfaction, the latter feeling hurt and betrayed, accounted for poor mentee outcomes in BBBS [ 18 ].…”
Section: Resultsmentioning
confidence: 99%
“…Researchers have found that mentor behavior that is consistent with Positive Youth Development Theory (PYD), which views youth as assets in possession of unique strengths to be developed, leads to the higher quality relationships (Lerner et al, 2013). These relationships mentors are collaborative, attuned to the mentee's needs, and share a purpose (Karcher et al, 2010; Pryce, 2012; Weiler et al, 2017). Highly effective mentors view their mentees as equal team members and work with their mentee rather than adopting a hierarchical approach to the relationship (Pryce, 2012).…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Through the mentoring relationship, mentors provide support to a youth's social and emotional functioning, strengthening cognitive abilities, and fostering positive identity formation (Rhodes, Spencer, Keller, Liang, & Noam, 2006). Although not all mentoring programs achieve the anticipated positive outcomes (Drake & Barnowski, 2006), those that do may reflect the ability of mentors to establish strong long-term prosocial bonds with adolescents (DeWitt, DuBois, Erdem, Larose, & Lipman, 2016) and be attentive to adolescent's support seeking behaviors (Weiler, Chesmore, Pryce, Haddock, & Rhodes, 2019). In one study of mentor characteristics associated with success, there was an interdependent connection between relationship quality and youths' outcomes (Silverstein, 2012).…”
Section: The Mentoring Rolementioning
confidence: 99%